The Goldilocks dilemma in coaching: women coaches' experiences of stereotypical biases and a two-dimensional approach to combat them - Gosai, J.; Jowett, S.; Rhind, D. J. (International Sport Coaching Journal, 2024)
The purpose of this study was to explore through semistructured interviews (a) the experiences of women coaches in relation to the stereotypical biases they may encounter in their workplace and (b) the strategies women coaches and sport organizations have, or can potentially put in place, to raise awareness and address these stereotypical biases. Content analysis of the obtained qualitative data using a rudimentary framework based upon the two sections of the interview schedule (i.e., dilemmas and strategies) guided categorization of the data. Findings indicated that women coaches experienced three broad types of stereotypical dilemmas: (a) extreme perceptions (e.g., too soft or too tough); (b) the high competence threshold (e.g., higher standards with lower rewards); and (c) competent but disliked (e.g., competent or likeable but rarely both). In addition, the findings indicated that tackling these stereotypical dilemmas effectively required a two-dimensional approach: individual and organizational. Within this paper, the authors discuss the ways women coaches both experience and confront a range of stereotypical dilemmas while moving into and through the coaching system. Such dilemmas inevitably disadvantaged women coaches by either slowing down or holding back their progress compared with their men coach counterparts. Practical solutions are also discussed.